Changing trends of causative factors in antenatal mothers with bad obstetric history: a retrospective study - W. B., Anu Bhargavi; R., Sailatha; C. R., Anuradha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The death of an infant, in utero or after birth has been a devastating experience for parents and clinicians alike. Various efforts are being made to make an accurate diagnosis of such pregnancy losses at the earliest to prevent the emotional and physical stress that the woman undergoes. This study aims to assess the changing trends in risk factors and outcome of pregnancies in cases of bad obstetric history (BOH) and to identify the newly emerging maternal and fetal factors contributing to incidence of pregnancy loss. Methods: This study is a retrospective analysis of antenatal women with BOH attending the obstetrics and gynecology OPD at Chettinad hospital. The study was conducted during a time period of 1 year (May 2019 to May 2020). Results: The medical complications and underlying causes for BOH were analysed among the study group. Out of 41 women, 6 were diagnosed to have gestational diabetes mellitus (GDM), 8 were found to be hypertensive and 1 APLA positive. Neonatal mortality was encountered in 2 cases, attributing to Inborn error of metabolism. However, the cause for BOH remained unexplained in 3 individuals. Conclusions: A full work-up can be initiated after two consecutive losses to identify and treat the various causes responsible for BOH. Lot of further studies and research are being conducted to unravel the mystery in these cases. Despite these efforts, the male factors contributing to recurrent pregnancy loss have remained largely unexplored.